Functional Safety Problematics of Vehicles in Relation to the Safety Related Requirements of the Safety Integrity Level (Current Problems in Rail Vehicles, 2021)
The article deals with current aspects of a significant part of the field of reliability, namely the issue of functional safety of railway vehicles in relation to the safety related requirements and system hardware architecture. This area is of course governed by a number of standards, but in this area and the application level, especially the standards EN 61508 and EN 50129. The fundamental steps related to the approval of vehicles and their components in terms of functional safety in this article have been described. Furthermore, the work with hardware architectures in connection to the safety related requirements of the safety integrity level SIL has been shown.
Keywords: functional safety; railway vehicles; reliability; hardware architectures